The Influence of Brand Image, Product Quality and Price Perception on Purchase Decisions on Camille Beauty Masks (Case Study on FEB Students of the Management Study Program Class of 2021, Universitas Bhayangkara Jakarta Raya) - Rahma Afrilia Putri; Neng Siti Komariah; Haryudi Anas (SEAN Institute, 2025)
This study aims to analyze the influence of Brand Image, Product Quality and Price Perception on the purchase decision of Camille Beauty Mask products. The research method used is the puposive sampling method by distributing questionnaires to respondents. The data analysis technique in this study uses SPSS version 26 analysis. The results show that Brand Image does not have a significant effect on purchase decisions, although it is statistically significant. On the other hand, the variables of Product Quality and Price Perception are the more dominant factors in influencing the purchase decision on Camille Beauty masks. This research provides important implications for companies to pay more attention to Product Quality and Price Perception factors to improve purchasing decisions among consumers.